Exploration beyond osteoarthritis: the association and mechanism of its related comorbidities - Li, Bo; Yang, Zhenguo; Li, Yang; Zhang, Jiuchao; Li, Chengen; Lv, Naishan (Frontiers in Endocrinology, 2024)
Osteoarthritis is the most prevalent age-related degenerative joint disease and a leading cause of pain and disability in aged people. Its etiology is multifaceted, involving factors such as biomechanics, pro-inflammatory mediators, genetics, and metabolism. Beyond its evident impact on joint functionality and the erosion of patients' quality of life, OA exhibits symbiotic relationships with various systemic diseases, giving rise to various complications. This review reveals OA's extensive impact, encompassing osteoporosis, sarcopenia, cardiovascular diseases, diabetes mellitus, neurological disorders, mental health, and even cancer. Shared inflammatory processes, genetic factors, and lifestyle elements link OA to these systemic conditions. Consequently, recognizing these connections and addressing them offers opportunities to enhance patient care and reduce the burden of 2 associated diseases, emphasizing the need for a holistic approach to managing OA and its complications.